Value stream mapping for identification and assessment of material waste in construction: A case study. Issue 8 (August 2019) - Vilventhan, Aneetha; Ram, VG; Sugumaran, S
Construction sites are plagued with numerous problems, such as improper planning and management, high amounts of waste generation and low awareness of waste reduction. Construction and demolition waste literature provides several best practises and prescriptive strategies that help minimise waste during construction. However, it lacks in the systematic identification and minimisation approach of all possibilities of waste. Therefore, studies focusing on principles and tools that help systematically analyse the inefficiencies of on-site processes leading to waste generation and philosophies addressing waste minimisation are necessary. As eliminating waste is one of the key lean principles, this article discusses the need and importance of integrating the lean construction with the construction and demolition waste management. This article aims to estimate and assess the causes of waste generation in a high-rise building construction through a case study in Chennai city (India) using value stream mapping, a key lean construction tool. Onsite monitoring and measurement were performed to quantify the amount of waste generated. A waste generation rate of 66.26 kg m −2 was identified, of which concrete, cement mortar and brick waste represented almost 90% of the total construction waste. Direct observation and interviews of site personnel were conducted to understand the causes of waste generation. A strategic framework has been proposed to improve construction and demolition waste minimisation depicting the synergy of combining lean construction principles with construction and demolition waste management strategies. The proposed framework helps in the systematic identification, assessment and minimisation of on-site construction waste generation.